PENDIDIKAN KARAKTER DALAM PERSPEKTIF PENDIDIKAN ISLAM - Fathurrahman, Muhammad (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Character education is the deliberate effort (conscious) to help people understand, care about, and implement core ethical values. Expectations character and personality are formed in self-learners that is the dream of success of character education. Learners are expected to understand the values imparted to him, entirely without any mis-understanding at all. Even learners will be expected to understand the development of these values. Koran which is the main source of Islamic education, a lot of mention about character education, but with an expression of character, almost every story contained in the Koran, in which there is character education.